A novel de novo intronic variant in ITPR1 causes Gillespie syndrome. Issue 8 (5th May 2021) - Keehan, Laura; Jiang, Ming‐Ming; Li, Xiaohui; Marom, Ronit; Dai, Hongzheng; Murdock, David; Liu, Pengfei; Hunter, Jill V.; Heaney, Jason D.; Robak, Laurie; Emrick, Lisa; Lotze, Timothy; et al.
Abstract: Gillespie syndrome (GLSP) is characterized by bilateral symmetric partial aplasia of the iris presenting as a fixed and large pupil, cerebellar hypoplasia with ataxia, congenital hypotonia, and varying levels of intellectual disability. GLSP is caused by either biallelic or heterozygous, dominant‐negative, pathogenic variants in ITPR1 . Here, we present a 5‐year‐old male with GLSP who was found to have a heterozygous, de novo intronic variant in ITPR1 (NM_001168272.1:c.5935‐17G > A) through genome sequencing (GS). Sanger sequencing of cDNA from this individual's fibroblasts showed the retention of 15 nucleotides from intron 45, which is predicted to cause an in‐frame insertion of five amino acids near the C‐terminal transmembrane domain of ITPR1. In addition, qPCR and cDNA sequencing demonstrated reduced expression of both ITPR1 alleles in fibroblasts when compared to parental samples. Given the close proximity of the predicted in‐frame amino acid insertion to the site of previously described heterozygous, de novo, dominant‐negative, pathogenic variants in GLSP, we predict that this variant also has a dominant‐negative effect on ITPR1 channel function. Overall, this is the first report of a de novo intronic variant causing GLSP, which emphasizes the utility of GS and cDNA studies for diagnosing patients with a clinical presentation of GLSP and negative clinical exome sequencing.